Burkina Faso : The Challenge of Export Diversification for a Landlocked Country - World Bank (Washington, DC, 2012)
The objective of the Diagnostic Trade Integration Study (DTIS) is to build the foundation for accelerated growth by enhancing the integration of its economy into regional and global markets. Burkina Faso is one of the best economic performers in West Africa, yet its integration into the world economy, as measured by its trade and foreign investment performance, is among the lowest. Economic growth has been strong, higher than all other countries in the sub-region. This has been achieved in spite of droughts and cricket invasions, and the turmoil in Cote d'Ivoire, and without significant oil or mining exports. Macroeconomic management has been consistently strong, and inflation low. At the same time, its export to gross domestic product (GDP) ratio is only one-third that of Senegal or Mali, while foreign directs investment inflows are far below the average for sub-Saharan Africa. At a time when globalization is determining the fate of nations, Burkina Faso seems to be on the sidelines and doing fairly well. If the country is to raise economic growth rates to the levels necessary to make major inroads on poverty, and reduce its aid dependence, it will need to improve its performance on exports and foreign investment. Implementation of a weighing program to fight against overloading of merchandise, coordinated along all the corridors.The challenge for Burkina Faso is to step up efforts to consolidate this sound performance in order to accelerate growth and deepen the fight against poverty. These efforts will be deployed on three fronts. The first consists in maintaining macroeconomic stability to improve the international competitiveness of the economy; the second, diversifying exports to expand trade and stimulate growth; and the third, strengthening social sectors and small operators in order to make growth inclusive and to maximize its impact on poverty reduction. This study focuses on the second challenge, taking into account the importance of participation by small operators.